SOCIAL AND RELIGIOUS DEVELOPMENT IN EARLY CHILDHOOD; IMPORTANT IMPLICATIONS IN EDUCATION - Sari, Mutia; Aisyah, Siti Ayu; Suryana, Ermis; Abdurrahmansyah, Abdurrahmansyah (Pusat Penerbitan Universitas (P2U) Unisba, 2023)
The social and religious development in early childhood is influenced by interactions with the environment and the role of education. Young children experience an increase in social skills and develop an understanding of religion influenced by fantasy and emotions. Religious education strengthens their faith foundation, shapes good character, and teaches values aligned with their religious beliefs. Factors such as family, educational environment, gender roles, peer influence, and religion impact the social and religious development of children. Parents and teachers play a crucial role in supporting this development through gradual learning strategies and integrated programs. Formal and non-formal education are instrumental in shaping children's mindset and behavior, while the environment helps filter positive influences. In conclusion, formal and non-formal education, parents, and teachers are essential in supporting the social and religious development of young children. This article employs a literature review methodology with secondary data collection and critical analysis of relevant sources such as books and journals. The descriptive presentation of the analysis provides an overview of the social and religious development in early childhood and its implications in education.